Formulation and aging resistance of modified bio-asphalt containing high percentage of waste cooking oil residues. (10th September 2017) - Sun, Daquan; Lu, Tong; Xiao, Feipeng; Zhu, Xingyi; Sun, Guoqiang
Abstract: Waste cooking oil residues (WCOR) based bio-asphalt is a potential substitute for petroleum asphalt. This study aims to prepare a bio-asphalt with high percentage of WCOR derived from esterification reaction for biodiesel. According to the uniform design results, the optimum mass ratios of materials were determined as WCOR of 33.3%, resin (RE-1) of 30.3%, hard asphalt particles (HAP) of 31.8%, low density polyethylene particles (LDPE) of 4.6% and linear SBS (L-SBS) of 4%. Based on the orthogonal design results, the WCOR based bio-asphalt would have the best performance when stirred for 40 min and sheared for 50 min (4000 rpm) under the condition of 170 °C with the optimum mass ratios. Rotational viscosity (RV) test results indicated that the viscosity of optimal bio-asphalt (OBA) was between PEN 70 base asphalt (PEN 70) and SBS modified asphalt (SBS-MA). Dynamic shear rheometer (DSR) test and bending beam rheometer (BBR) test results proved that OBA exhibited excellent high-temperature performance similar with SBS-MA, and it had superior low-temperature performance to SBS-MA and PEN 70. Furthermore, the effect of thermo-oxidative aging on the properties of OBA was studied. DSR test results revealed that the complex modulus and phase angle of thin film oven (TFO)-aged OBA both increased with the elevated aging level, indicating an increase in viscosity during aging process. Fourier transform infrared spectroscopy (FTIR) test results showed that there was no obvious variation on the functional groups of OBA after 15 h TFOT aging process. It was confirmed that less aging susceptibility of OBA was found compared with PEN 70, which demonstrated that OBA had a better aging resistance performance.